Project overview, objectives and implementation - Olaloku, E.A. (International Livestock Centre for Africa, 1994)
This paper outlines Africa's food problem, the livestock production situation, how research can contribute, institutional roles, and the networking approach. It describes the project with particular reference to project background, problem, project objectives, project implementation and expected outputs.